THE REGULATION OF MARRIAGE AND FAMILY RELATIONS IN MEDIEVAL MONGOLIA - Serzhena Zhigmitovna Dugarova (Science and Innovation Center Publishing House, 2016)
Legal anthropology studies of the institution of marriage and family focusing on sources and form of matrimonial law have featured conflicting conclusions. In scientific literature the disputes among researchers are settled by defining one’s views on the theory of customary law. The article contains analysis of institution of marriage and family under customary law of medieval Mongolia. In traditional Mongolian society the oral rules of customary law that defined the foundations of social order and reflected the nomads’ world view were never altered, even in the era of big changes. Customary law that regulated such an important part of society as matrimonial relations was eagerly protected by society and the state. Written records of matrimonial norms were caused by exceptional circumstances. Dictations of the nomadic state were intended whether to anchor social reformations for the benefit of the state or to defend the social values depreciated by new environment. The analysis allowed to conclude consistency and features peculiar to marriage and family evolution under Mongolian customary law as part of law and the legal system of the Mongolian state. Purpose: to analyze the institution of marriage and family of medieval Mongolia under Mongolian customary law. Methodology: the comparative method, the dogmatic method: analogy, analysis, synthesis. Results: the characteristics of the development and validity degree of statements on the history of marriage and family law of medieval Mongolia put forward in the scientific literature. Application of results: the results obtained can be used in the preparation of general works on the history of nomadic nations and the history of the Mongolian state and law.